Efektivitas Kompres Panas pada Lansia dengan Gejala Osteoarthritis terhadap Skala Nyeri dan Skala Fungsional di Panti Sosial Budi Agung Kota Kupang - Ramadani, Tiara (Universitas Nusa Cendana, 2024)
Background: Osteoarthritis is the most common degenerative disease in the musculoskeletal system and is chronic. Osteoarthritis is most common in the knee, hand, and hip joints and most often affects the elderly. Objective: Knowing the effectiveness of hot compress therapy in the elderly with Osteoarthritis symptoms on the pain scale and functional. Methods: The type and design of the study was pre-experimental with one-group pretest-posttest. Researchers take measurements before treatment and then compare with after treatment. The sample amounted to 26 people and the difference test between the two groups was tested using the Wilcoxon Signed Rank Test method. Results: The majority of the pain scale before the intervention was pain and more pain (30.8%) while after the intervention was less pain (38.5%). The majority of the functional scale before the intervention was moderate (65.4%) while after the intervention was mild (84.6%). From the results of the Wilcoxon Signed Rank Test there was a significant difference with a p value <0.001 (significant p<0.05). Conclusion: Hot compresses are effective in reducing the pain scale and functional scale where there is a significant decrease in the pain scale and functional scale after the hot compress intervention twice a day for seven days.